Technological Demonstration and Life Cycle Assessment of a Negative Emission Value Chain in the Swiss Concrete Sector - Tiefenthaler, Johannes; Braune, Lisa; Bauer, Christian; Sacchi, Romain; Mazzotti, Marco (Frontiers in Climate, 2021)
Switzerland, such as most of the other countries which are part of the Paris agreement, decided to reduce GHG emissions to zero by 2050. The ambition of net-zero GHG emission across all industrial sectors can only be achieved by rapid decarbonization and the deployment of negative emission technologies to compensate residual emissions from for example agriculture. In the scope of this work, the proof of technology of a negative emission value chain at industrial scale in the concrete sector is presented. The core of the system is a mineralization technology, which fixes biogenic CO$_2$ permanently as calcium carbonate in concrete aggregate. In addition, the net-negativity in terms of GHG emissions and environmental burdens beyond these are quantified in a Life Cycle Assessment (LCA). It could be shown that an industrial-scale mineral carbonation process can be seamlessly integrated in today's concrete recycling processes and that it can process relevant amounts of concrete aggregate while storing on average 7.2 kg CO$_2$ per ton of concrete aggregate. Moreover, material tests revealed that the carbonated concrete aggregate fulfills the same service as the regular one - thus no significant effects on the concrete properties could be observed. The LCA shows that every processing step requires materials and energy, and thus generates associated emissions. However, from a cradle to gate perspective, the carbon removal efficiency is 93.6%. Thus, 1000 kg of CO$_2$ stored generate 64 kg of CO$_2$-eq. emissions. Furthermore, it could be shown that biogas upgrading can supply sufficient amounts of CO$_2$ until 2030 in Switzerland. From 2030 on, more and more CO$_2$ from other emission sources, such as waste incineration, need to be utilized to exploit the full potential of the value chain, which is going to be 560 kt of negative CO$_2$ emissions in Switzerland in 2050, corresponding to 30% of the projected demand within the national borders.